Investigating the Strategies Employed by McDonald's to Establish Sustainable Customer Relationships - Ban, Teoh Kok; Lee, Jia Lin Jocelyne; Volha, Rudkouskaya; Zamri, Muhammad Syazwan Afifi Bin; Azian, Nadiah Hidayah Binti; Ng, Pei Long; Maulana, Zulkifli Ega Irvan; Via, Seviana; Vladimir, Gerasimenko; Kee, Daisy Mui Hung (AIBPM Publisher, 2024)
McDonald's Corporation, established in 1940, is an American multinational fast-food chain. Over the years, McDonald's has successfully expanded their business operation worldwide. The customer plays a vital role in the success of a business. The strategies and abilities to retain a customer will determine the survival of a business. Hence, this paper aims to examine the strategies employed by McDonald's to establish sustainable customer relationships. To explore, primary and secondary data collection was conducted through several sources, and a digital questionnaire was produced to collect data and information from 150 respondents.. The hypothesis of this study is to examine whether the independent variables, such as food quality, service quality, atmosphere, price, and Brand and influence, influence the dependent variable, customer relationship. This paper will explore the contribution relationship between food quality, service quality, Atmosphere, Price, and Brand and their influence on McDonald's sustainable customer relationship and to better understand its correlations. Recommendations and implications were discussed